Uptake of Some Elements with Aquatic Plants Exposed to the Effluent of Wastewater Treatment Plant - Tatar, S.; Obek, E.; Topal, Arsian E., I; Topal, M. (Univ Tehran, 2019)
In this study, in the removal of macro (P, S, Na, K, Ca, Mg) and micro (Sb, Ba, Co, Cu, Fe, Pb, Mn, Hg, Mo, Se, Ag, Zn) elements in the effluent of Elazig Wastewater Treatment Plant, the efficiency of Lemna minor L. and Lemna gibba L. has been studied comparatively. For this aim, fronds of these plants have been adapted to the effluent of the treatment plant that feeds pilot scale reactors. The concentrations of elements in fronds harvested during the working period were analyzed by ICP/MS. The analytical results show that Lemna minor L. has a high accumulation potential for P, Sb, Ba, Co, Fe, Pb, Mn, Hg, Ag and Zn while Lemna gibba L. has a high accumulation potential for S, Na, Ca, Mg, Cu, Mo and Se. The results show that Lemna minor L. and Lemna gibba L. can be used as phytoremediators of wastewater.
Keywords: Accumulation; Lemna gibba L.; Lemna minor L.; phytoremediation; wastewater